Structural Characteristics of HLA-DQ that May Impact DM Editing and Susceptibility to Type-1 Diabetes - Jensen, Peter E.; Zhou, Zemin (Frontiers in Immunology, 2013)
Autoreactive CD4+ T cells initiate the chronic autoimmune disease Type-1 diabetes (T1D), in which multiple environmental and genetic factors are involved. The association of HLA, especially the DR-DQ loci, with risk for T1D is well documented. However, the molecular mechanisms are poorly understood. In this review, we explore the structural characteristics of HLA-DQ and the role of HLA-DM function as they may contribute to an understanding of autoreactive T cell development in T1D.